Early Experience With Interleukin-6 Receptor Antagonists in Patients With COVID-19 Admitted to a Community Hospital. (October 2022) - Manning, Kyle; Whitman, Chris; Hohmann, Lindsey; Tubbs, Jessica; Childress, Darrell; Leon de la Rocha, Jose A.
Background/objective: The efficacy of interleukin-6 (IL-6) inhibitors in hospitalized patients with severe coronavirus disease 2019 (COVID-19) pneumonitis is unclear.Method: This retrospective, observational cohort study included patients hospitalized at a community hospital with COVID-19 pneumonia from March 2020 to May 2020. All patients were treated with standard of care (SOC), and a nonrandomly selected subset of patients also received an IL-6 inhibitor. The primary outcome was clinical response, defined as an improvement of at least 2 categories relative to baseline on a 7-category ordinal scale up to hospital discharge or 30 days. In adjusted analyses, logistic and linear regression models were conducted, controlling for covariates of hospital length of stay (LOS), intensive care unit (ICU) care, ICU LOS, gender, age, race, and Charlson Comorbidity Index.Results: A total of 133 patients met inclusion criteria. In all, 30 patients received an IL-6 inhibitor plus SOC. There was no statistical difference in clinical outcome between groups as 76.7% in the SOC alone group and 70.0% in the IL-6 inhibitor group met the defined endpoints for clinical response ( P = 0.477). In the adjusted analysis, patients treated with IL-6 inhibitors were approximately 4 times more likely to meet the primary endpoint compared with patients with SOC alone (adj. odds ratio = 4.325; P = 0.038, 95% confidence interval = [1.09-17.18]).Conclusions: Compared with SOC alone, IL-6 inhibitors were not associated with a significant clinical response. However, after adjusting for covariates, this study suggests that the initiation of IL-6 inhibitors in patients with early COVID-19 pneumonitis before progression to the ICU may be associated with improved clinical status.